CONTEMPORARY PEDAGOGICAL MECHANISMS FOR ENHANCING DIGITAL COMPETENCE IN VOCATIONAL EDUCATION TEACHERS (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
The article analyzes mechanisms for developing digital competence among professional education teachers. Virtual classes, online trainings, and digital platforms enhance professional skills, creative thinking, and effective use of ICT.